2021
DOI: 10.1155/2021/4355805
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Value of Colposcope Combined with Serum Squamous Cell Carcinoma Antigen, Carbohydrate Antigen 125, and Carcinoembryonic Antigen for Moderate to Advanced Cervical Cancer Patients Treated with Modified Fuzheng Peiyuan Decoction

Abstract: Objective. To explore the diagnosis value of colposcope combined with serum squamous cell carcinoma antigen (SCC-Ag), carbohydrate antigen 125 (CA125), and carcinoembryonic antigen (CEA) for moderate to advanced cervical cancer patients treated with modified Fuzheng Peiyuan decoction. Methods. The clinical data of 43 moderate to advanced cervical cancer patients treated in Suzhou Hospital of Traditional Chinese Medicine from July 2018 to July 2019 were selected for the retrospective analysis, and 43 healthy wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, the determination of tumor markers presence or content could be used to diagnose the generation of malignant tumors, analyze the patient's condition, monitor metastasis, and judge the prognosis of patients [26]. CEA is an acid glycoprotein isolated from embryonic colon mucosa and colon adenocarcinoma which is expressed on the surface of tissue cell membrane and is widely used in the differential diagnosis of malignant tumors [27]. CA125 is a mucin-like glycoprotein with high molecular weight which can promote cell metastasis and infiltration by influencing mutual recognition and adhesion among cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the determination of tumor markers presence or content could be used to diagnose the generation of malignant tumors, analyze the patient's condition, monitor metastasis, and judge the prognosis of patients [26]. CEA is an acid glycoprotein isolated from embryonic colon mucosa and colon adenocarcinoma which is expressed on the surface of tissue cell membrane and is widely used in the differential diagnosis of malignant tumors [27]. CA125 is a mucin-like glycoprotein with high molecular weight which can promote cell metastasis and infiltration by influencing mutual recognition and adhesion among cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Serum tumor markers play an important role in the monitoring of cervical cancer and are independent prognostic factors. Many studies have confirmed that squamous cell carcinoma antigen (SCC-Ag), cancer antigen 125 (CA125), carcino-embryonic antigen (CEA) play an important role to evaluate prognosis, therapeutic response, local recurrence and distant metastasis in cervical squamous cell carcinoma and adenocacinoma ( Dasari et al, 2015 , Lee et al, 2021 , Zhou et al, 2017 , Huang et al, 2020 , Meng et al, 2021 , Volkova et al, 2021 , Bender et al, 2003 Jul , Kubota et al, 2019 ). For relatively concealed lesions, when no lesions that can explain the symptoms are found in the routine imaging examination and the serum tumor markers increase at the same time, MRI examinationis should be recommended to determine whether there is SEM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the determination of tumor markers presence or content could be used to diagnose the generation of malignant tumors, analyze the patient's condition, monitor metastasis, and judge the prognosis of patients [26]. CEA is an acid glycoprotein isolated from embryonic colon mucosa and colon adenocarci-noma which is expressed on the surface of tissue cell membrane and is widely used in the differential diagnosis of malignant tumors [27]. CA125 is a mucin-like glycoprotein with high molecular weight which can promote cell metastasis and infiltration by influencing mutual recognition and adhesion among cells [28].…”
Section: Discussionmentioning
confidence: 99%